Reigen, Band 1 Historisch-kritische Ausgabe - Schnitzler, Arthur (Walter de Gruyter GmbH, 2019)
Historical-critical edition of Arthur Schnitzler's "Reigen." This edition presents a comprehensive preface analyzing above all the text genesis and the complex printing history, the manuscripts with transcriptions, a print text with a display of textual variants and a commentary.